The ‘island of silver veins’: an overview of the earliest metal and metalworking in Sardinia - Pearce, Mark (Deutsches Bergbau-Museum Bochum, 2018)
This paper presents a review of our knowledge of the earliest phases of metal use and working in Sardinia, based where possible on radiocarbon chronology. It covers the cultural periods from the late Neolithic Ozieri to the Copper Age Monte Claro phase. I suggest that in contrast to continental Italy, the earliest metalwork in Sardinia seems to be used for display. It is striking that metal use and working seems to emerge in Sardinia later than in mainland Italy, despite the island’s rich metal resources.